2016
DOI: 10.1097/fjc.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Oleanolic Acid in Human Umbilical Vascular Endothelial Cells is Mediated Via UCP2/ROS/Cytochrome C/AIF Pathway

Abstract: The aim of this study is to assess the potential protective effect of oleanolic acid (OA) against ox-LDL induced damage in human umbilical vascular endothelial cells (HUVECs) and investigate potential mechanism of action including antioxidative effects and inhibition of mitochondria apoptosis pathway. Cell counting kit 8 was used to evaluate the viability of HUVECs. 2', 7'-DCFH-DA staining and flow cytometry was used to assess the levels of intracellular reactive oxygen species in HUVECs. The protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The prevention of VSMC proliferation is among the most promising atherosclerosis prevention strategies, in which oxidative stress and inflammatory cytokines are crucial factors to consider (Li et al, ). On the other hand, OA was known for its antioxidant and anti‐inflammation effects (Tsai and Yin, ; Kong et al, ). In vivo studies also revealed that OA exerted anti‐atherosclerotic effects (Jiang et al, ); however, the role of OA in VSMC proliferation had yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevention of VSMC proliferation is among the most promising atherosclerosis prevention strategies, in which oxidative stress and inflammatory cytokines are crucial factors to consider (Li et al, ). On the other hand, OA was known for its antioxidant and anti‐inflammation effects (Tsai and Yin, ; Kong et al, ). In vivo studies also revealed that OA exerted anti‐atherosclerotic effects (Jiang et al, ); however, the role of OA in VSMC proliferation had yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…OA has been reported to exert various benefits, including hypolipidemic, hepatoprotective, and anti-tumor effects (Kim et al, 2005;Jiang et al, 2015;Guo et al, 2017). In vitro studies had revealed its antioxidative and anti-inflammatory effects (Tsai and Yin, 2008;Jiang et al, 2015;Kong et al, 2016). However, previous studies had not investigated its potential effects on VSMCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, ow cytometry was utilized to quantitatively evaluate the apoptosis rate of DA neurons. The intracellular ROS production in primary DA neurons was detected utilizing ow cytometry with uorescent DCFH-DA as probe (Enzo Life Sciences) [17] .The mPTP opening of primary DA neurons was evaluated with a ow cytometer after CoCl 2 -calcein uorescence quenching assay [18]. The data of aforementioned three assay were processed with CellQuest Pro software (BD Bioscience).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Oleanolic acid (OLA) is a natural pentacyclic triterpenoid compound mainly extracted from Fructus Ligustri Lucidi (the fruit of Ligustrum lucidum ), which is an important Chinese herbal medicine for protecting against inflammation, osteoporosis and endocrine metabolic disorders . Numerous studies reveal that OLA has the ability to block stimuli‐induced cell apoptosis, including podocyte, lung epithelial cell and human umbilical vascular endothelial cells . Several studies suggest that OLA has a beneficial effect on injury‐induced metabolic disorders of articular cartilage .…”
Section: Introductionmentioning
confidence: 99%